The inverter with reverse connected double converter driving unbalanced loads. (4th March 2022) - Can, Erol
ABSTRACT: Inverter circuits play an important role in providing energy to multiple loads or energy lines. In cases where power lines or loads are unbalanced, it is important to balance and regulate the power it carries. Therefore, in this study, an inverter structure with an inverted connecting double dc-dc converter is used to drive unbalanced loads. While load balancing is performed by changing the widths of the pulse width modulation that make up the voltage in load balancing methods in other inverter studies, the maximum point of the generated voltage is changed by affecting the operating times of the converters in this study. First, the circuit structure and the working order of the circuit are given. Then three-phase balanced and unbalanced loads are driven. The unbalanced loads driven are finally balanced with the proposed circuit structure. Distortions of load currents are decreased as %3, 51. This distortion value is lower than 4% reported by the international IEEE, while the obtained load currents maintain a smooth sinusoidal structure.